Peningkatan kemampuan pemecahan masalah, berpikir kreatif dan self-confidence siswa melalui model pembelajaran berbasis masalah - Sofi Nurqolbiah (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to investigate: (1) the differences in the achievement and improvement of student’s mathematical problem solving between problem-based learning class and scientific approach class; (2) the differences in the improvement of student’s mathematical problem solving between problem-based learning class and scientific approach class; (3) the differences in the achievement and improvement of student’s mathematical creative thinking between problem-based learning class and scientific approach class; (4) the differences in the improvement of student’s mathematical creative thinking between problem-based learning class and scientific approach class; (5) the differences in student’s self-confidence between problem-based learning class and scientific approach class. This research was a quasi-experimental research through problem-based learning approach and scientific approach. The population of the study were all students of class X in one of SMK in Bandung and two classes were taken as the sample. The research instruments used were the problem-solving test, mathematical creative thinking tests and self-confidence questionnaires. The results showed that there were differences in the achievement and improvement of student’s problem-solving skills, mathematical creative thinking and self-confidence in both class groups experiments.